Îles-frontières, territoires impossibles? - Pelletier, Philippe (Études internationales, 1997)
Japan has a tradition of borders, not only at sea but also on land. Given the country's insularity and historical development, the former kind are the ones that will be of concern to international relations. Their demarcation, and the disputes that may arise with adjacent maritime countries (Russia, China, Korea), are a legacy of both history and geography. A remote island is not necessarily an ideal point for marking off a territory, as exemplified by the Takeshima/Tok-to islets which Japan and Korea have been disputing. The recent delimitation of maritime Exclusive Economic Zones is raising the stakes and stirring up tensions.